Synthesis of Some Cyclophosphorodiamidates Derivatives of Bis(2-chloroethyl)amine - Jalalifar, Mahdi; Khalikov, Shirinbek; Javidan, Abdollah (Asian Journal of Chemistry, 2013)
Phenyl phosphorodichloridate (1) is readily prepared by reaction of phenol with phosphoryl chloride at low temperature. The crude product is white in colour is subjected to vacuum distillation. However, this reagent reacts only poorly with bis(2-chloroethyl)amine hydrochloride at ambient temperature; thus, an alternative route was sought to aniline and to give 2 and 3, respectively compounds. Compound (3) reacted with aniline and diazabicyclo[2,2,2]octane in refluxing toluene to give 4. Reaction of 3 with diazabicyclo[2,2,2]octane and potassium tert-butoxide in refluxing toluene gave 5 and 6, respectively which compound 6 arised from elimination of HCl from the 2-chloroethyl group of compound 5. Reactions proceed in high yield, under mild conditions. The structures of prepared compounds were confirmed by 1H, 31P and 13C NMR spectroscopy, mass spectrometry and X-ray crystallography.